2009
DOI: 10.1177/089686080902902s10
|View full text |Cite
|
Sign up to set email alerts
|

Quantitation of Markers of Protein Damage by Glycation, Oxidation, and Nitration in Peritoneal Dialysis

Abstract: Proteolysis products of proteins damaged by glycation, oxidation, and nitration—glycated, oxidized, and nitrated amino acids (glycation, oxidation, and nitration free adducts)—are waste products normally excreted in urine and cleared in peritoneal dialysate. Glucose degradation products in peritoneal dialysis (PD) fluids may increase protein damage, giving rise to increased protein glycation, oxidation, and nitration adduct residues of proteins and increased flux of glycation, oxidation, and nitration free add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Oxidative stress during peritoneal dialysis has been established in many studies. 22,23 Generation of oxidative stress products such as reactive oxygen species (ROS) and MPO by conventional peritoneal dialysis solutions has been claimed responsible for progressive membrane dysfunction 24 and the level of different ROS has been used to check for the level of oxidative stress in these patients. Numerous studies have reported that the elevated levels of oxidative stress and inflammation in dialysis patients are associated with arterial stiffness and in turn with the development of CVD.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress during peritoneal dialysis has been established in many studies. 22,23 Generation of oxidative stress products such as reactive oxygen species (ROS) and MPO by conventional peritoneal dialysis solutions has been claimed responsible for progressive membrane dysfunction 24 and the level of different ROS has been used to check for the level of oxidative stress in these patients. Numerous studies have reported that the elevated levels of oxidative stress and inflammation in dialysis patients are associated with arterial stiffness and in turn with the development of CVD.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, analysis at the level of individual amino acids (either free, or obtained by exhaustive hydrolysis of proteins) is the most straightforward and direct way to characterize the structures and quantities of glycation products, occurring in artificial and natural systems [ 86 ]. Therefore, the employed analytical strategies most commonly rely on amino acid analysis protocols, and provide a direct access to absolute quantities of individual glycation adduct classes (as well as unmodified amino acids) in biological samples of various origin and complexity [ 65 ].…”
Section: Methods Of Amino Acid Analysis In Glycation Researchmentioning
confidence: 99%
“…Reliable biomarkers are required for this purpose and many biomarkers have been applied to measure the level of oxidative stress in vivo [1,7,32]. Various oxidation products of lipids [33][34][35], proteins [36,37], and DNA [38] have been used as oxidative stress biomarkers as summarized in Table 2. Isoprostanes formed by the free radical-mediated oxidation of arachidonates are accepted to be most reliable biomarker of oxidative stress in vivo.…”
Section: Assessment Of Antioxidant Capacity In Vivomentioning
confidence: 99%